Habituation of Clean and Living Behavioers to Prevent Disease in Children at TK Pertiwi Pamekasan - Nisael Amala; Renanda Sabila Komariyah (Universitas muhammadiyah Banjarmasin, 2024)
This research aims to determine the habituation of clean and healthy living behavior to prevent disease in children at Pertiwi Pamekasan Kindergarten. Where many children do not go to school because of illness, such as flu, fever and others. So this PHBS refraction is very important to implement in Pertiwi Kindergarten. This research is a qualitative descriptive study. The informants in this study were 1 school principal, 4 teachers and 1 parent. The data collection method was carried out using observation, interviews and documentation techniques, while the data analysis techniques in this research were data reduction, data presentation and conclusions. The results of this research show that the application of clean and healthy living behavior to prevent disease in children that is implemented in this kindergarten is throwing rubbish in the right place and washing hands with soap and running water. In this refraction, the school principal acts as a facilitator who facilitates facilities and infrastructure. Teachers act as motivators, mentors, role models and directors for children to implement PHBS in the school environment. Meanwhile, parents act as directors and mentors when the child is in the home environment. There are several factors in this refraction, including limited adequate facilities and infrastructure, such as not having a water tap and only having 1 trash can and no waste selection. So the principal at TK Pertiwi Pamekasan needs to pay attention to this PHBS refraction so that fewer children contract the disease